Vaccination in the Time Of COVID-19: Survey Study at the University of Tlemcen in the Spring of 2022 (Journal of Epidemiology and Public Health, 2023)
Background: The novel human coronavirus SARS-CoV-2 causing COVID-19 with symptoms ranging from the common cold to pneumonia, has been responsible for the current health crisis, it has spread rapidly at record speed leaving many deaths of different ages and different ethnicities, and in order to stop this propagation, scientists rushed to create several efficient vaccines against this virus, and despite being marketed in all countries of the world, opinions diverged between supporters and opponents. This prompted us to carry out this survey study on vaccination against COVID-19 at the University of Tlemcen, with the aim of exploring the perceptions and opinions of participants on vaccination and vaccines in general.Subjects dan Method: A cross-sectional study was conducted over a two months period, using a questionnaire to collect data from Teachers and Students of the University of Tlemcen with a 382 calculated sample size, the survey was shared via email and social media networks. Variables of interest included exposure to the pathogen, the laboratory testing results, effectiveness and adherence to the preventive measures, while also monitoring the vaccine acceptance and hesitancy. Descriptive and statistical analysis were run on SPSS Statistics with a p-value